2018
DOI: 10.1002/cbic.201800181
|View full text |Cite
|
Sign up to set email alerts
|

Loop Protein Engineering for Improved Transglycosylation Activity of a β‐N‐Acetylhexosaminidase

Abstract: Certain enzymes of the glycoside hydrolase family 20 (GH20) exert transglycosylation activity and catalyze the transfer of β-N-acetylglucosamine (GlcNAc) from a chitobiose donor to lactose to produce lacto-N-triose II (LNT2), a key human milk oligosaccharide backbone moiety. The present work is aimed at increasing the transglycosylation activity of two selected hexosaminidases, HEX1 and HEX2, to synthesize LNT2 from lactose and chitobiose. Peptide pattern recognition analysis was used to categorize all GH20 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…Lastly, we would like to highlight a potential hotspot for mutations that drive trans-glycosylation activity in GH20 enzymes. We previously demonstrated that introduction of a specific loop, which was identified in related GH20 sequences from pathogens, into Hex1 led to a >5-fold increased trans-glycosylation product yield in reactions with Lac as acceptor and (GlcNAc) 2 as donor ( Figure 7B, Table 8) [117]. Additionally, in a recent mutational study on BbhI, the mutant W805R ( Figure 7A) was identified as the one with superior trans-glycosylation activity [104].…”
Section: A Non-conserved Loop Close To the Active Site As Hotspot Formentioning
confidence: 87%
See 3 more Smart Citations
“…Lastly, we would like to highlight a potential hotspot for mutations that drive trans-glycosylation activity in GH20 enzymes. We previously demonstrated that introduction of a specific loop, which was identified in related GH20 sequences from pathogens, into Hex1 led to a >5-fold increased trans-glycosylation product yield in reactions with Lac as acceptor and (GlcNAc) 2 as donor ( Figure 7B, Table 8) [117]. Additionally, in a recent mutational study on BbhI, the mutant W805R ( Figure 7A) was identified as the one with superior trans-glycosylation activity [104].…”
Section: A Non-conserved Loop Close To the Active Site As Hotspot Formentioning
confidence: 87%
“…Although chitin, e.g., from shrimp or crab waste streams, may seem an obvious substrate for sustainable β-N-acetylhexosaminidase catalyzed trans- Figure 7. Active sites models of two bacterial β-N-acetylhexosaminidases: (A) homology model of BbhI from Bifidobacterium bifidum (created with YASARA [138]) with the mutated W805 [104] highlighted in orange and GlcNAc bound in the active site; (B) homology model of Hex1GTEPG [117] with the inserted loop highlighted in red and the newly positioned R360 in orange; the reaction intermediate Glc-oxa was docked into the structure [117]. The catalytic Asp-Glu pair is highlighted in yellow, the water-stabilizing Tyr residue is highlighted in purple, bound or docked ligands are highlighted in green, and conserved residues (Arg and Trp) are highlighted in dark blue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different retention times of the compounds are assumed to derive from different positions of the methyl and/or acetyl substitutions. The porous graphite column in use has previously shown the capability to separate different isomers of compounds with identical molecular composition, but with different linkages and/or planarity (Jamek et al, 2018;Mosbech et al, 2018;Zeuner et al, 2018).…”
Section: Enzymementioning
confidence: 99%